Living Memories of Domestic Slavery versus Forced Labour: Freedom, dependence and oppression (Ibo Island, Cabo Delgado) - Francesca Declich (Cadernos de Estudos Africanos)
Living memories of slavery in the Querimbas Islands, especially Ibo Island, are apt to reserve some surprises. When talking about slavery, some elders’ shared memories sometimes seem to be defensive, serving to justify the practice of slavery rather than decrying it. This may be ascribed to several factors. The reasons which lie behind this viewpoint seem to be related to recent past events in which forced labour and political repression of dissent were extremely cruel as to obscure the mistreatment of slaves. This paper will inquire into the memories of forced labourers and descendants of domestic slaves as well as into the policies that preserved servants from being coerced into forced labour.